'Preciosa, Run Preciosa!': Lorca Reads Cervantes. Issue 8 (13th September 2020) - Davidi, Einat
Abstract: In this essay I examine a case of intertextuality in which Lorca refers to Cervantes. In Cervantes' novella La gitanilla (1613) Lorca identified two themes with which he engaged creatively in his early work, the feminine and the figure of the Gypsy; themes that in Cervantes are moulded into a single character—Preciosa, to become the quintessential Gypsy of Spanish literature. In the romance Preciosa y el aire from Romancero Gitano (1928) Lorca took the mythical Gypsy girl and created a new myth, without 'destroying' or 'murdering' the parent text, a move that I will characterize as 'activist poetics'.